Quick impact initiatives for gender equality: a menu of options - Caren A. Grown (Levy Economics Institute of Bard College, 2006)
The UN Millennium Project identified a set of Quick Impact Initiatives (QIIs) for achieving the Millennium Development Goals (MDGs). According to the Millennium Project, QIIs are interventions to be implemented in the early years of an MDG scale-up strategy that generate rapid results. With adequate resources, they can be implemented quickly (e.g., within three years) without large investments in infrastructure or capacity. This paper suggests some criteria that donors and governments can use to identify such initiatives for gender equality and uses those criteria to develop a broader menu of QIIs for gender equality and women's empowerment in low- and middle-income countries. It focuses particularly on Quick Impact Initiatives to promote women's economic opportunities.
Keywords: H5; J16; O2; 330; Millennium Development Goals; gender equality; quick impact initiatives; economic opportunity; education; employment; rural infrastructure; reproductive health; violence against women